РОЗВИТОК СИСТЕМ ПЛІВКОВОГО ОХОЛОДЖЕННЯ ЛОПАТОК ГАЗОВИХ ТУРБІН - Khalatov, А.А.; Borisov, І.І.; Kulishov, S.B. (Institute of Engineering Thermophysics of NAS of Ukraine, 2022)
The analysis of trends in the development of film cooling systems for gas turbine blades is carried out. The historical aspects and chronology of the development of film cooling technologies are presented.  Modern and promising schemes are considered, their comparative analysis is made. It is shown that the main way of the improvement of cooling systems is the use of shaped and anti-vortex openings, as well as the supply of coolant into recesses of various shapes. The effect of the conditions of coolant entry into the blowing hole from the internal channel is analyzed.